2020
DOI: 10.3390/molecules25153352
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid and Non-Flavonoid Compounds of Autumn Royal and Egnatia Grape Skin Extracts Affect Membrane PUFA’s Profile and Cell Morphology in Human Colon Cancer Cell Lines

Abstract: Grapes contain many flavonoid and non-flavonoid compounds with anticancer effects. In this work we fully characterized the polyphenolic profile of two grape skin extracts (GSEs), Autumn Royal and Egnatia, and assessed their effects on Polyunsaturated Fatty Acid (PUFA) membrane levels of Caco2 and SW480 human colon cancer cell lines. Gene expression of 15-lipoxygenase-1 (15-LOX-1), and peroxisome proliferator-activated receptor gamma (PPAR-γ), as well as cell morphology, were evaluated. The polyphenolic composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Polyphenolic profiles were determined by Ultra‐High‐Performance Liquid Chromatography/Quadrupole‐Time of Flight mass spectrometry (UHPLC/QTOF) analysis as previously the study reported. [ 49 ]…”
Section: Methodsmentioning
confidence: 99%
“…Polyphenolic profiles were determined by Ultra‐High‐Performance Liquid Chromatography/Quadrupole‐Time of Flight mass spectrometry (UHPLC/QTOF) analysis as previously the study reported. [ 49 ]…”
Section: Methodsmentioning
confidence: 99%
“…The polyphenolic composition of grapes, which depends on genotype, environmental factors and agronomic practices [ 104 ], affects the structural components of the cytoskeleton, cellular adhesions, and the cell membrane fatty acids profile [ 104 ]. Briefly, Figure 4 shows the main results obtained by our studies on grape skin and grape pomace extracts, as below.…”
Section: Fruit Componentsmentioning
confidence: 99%
“…The results of in vitro studies highlighted that Autumn Royal and Egnatia grape skin extracts influenced the gene expression of 15-LOX-1 and PPAR-γ. In particular, grape skin extracts polyphenols induced a significant upregulation of both 15-LOX-1 and PPAR-γ [ 104 ]. Together, these activated factors are required for the inhibition of the colorectal tumorigenesis process.…”
Section: Fruit Componentsmentioning
confidence: 99%
“…Experimental in vitro studies have shown an increase in total polyunsaturated fatty acids (PUFAs) levels in cells treated with Autumn Royal table grape extracts [ 11 , 12 ]. In particular, compared to untreated control cells, the grape extracts caused an increase in essential fatty acids (EFAs), namely linoleic acid (LA) and α-linolenic acid (ALA).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, compared to untreated control cells, the grape extracts caused an increase in essential fatty acids (EFAs), namely linoleic acid (LA) and α-linolenic acid (ALA). In addition, in cell membranes, the grape treatment exerted a significant increase in total PUFAs, associated with changes in their downstream metabolic pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%